1993
DOI: 10.1002/nur.4770160207
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical health and psychological well‐being in elderly women: A developmental perspective

Abstract: Little is known about the physical health and psychological well-being of very old women, although they are one of the fastest growing segments of the population. The relationships among physical health, psychological well-being, and age were investigated using a developmental perspective and a multidimensional approach to the assessment of psychological well-being. Two hundred and forty-three elderly women completed multiple self-report measures of physical health status and psychological well-being. Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 23 publications
3
35
0
1
Order By: Relevance
“…Younger age, gender, higher socio-economic status, better health status and self-rated health, better functional status and cognitive performance and extensive social relationships are some of the factors that may positively contribute to or confound and modify the associations of activity and subjective well-being (Beekman et al, 1998;Cummings, 2002;Diener, 1984;Everard, 1999;Heidrich, 1993;Heikkinen, Berg, & Avlund, 1995;Palsson & Skoog, 1997;Tijhuis, De Jong-Gierveld, Feskens, & Kromhout, 1999). The intensity of these associations has varied in different studies.…”
Section: Introductionmentioning
confidence: 92%
“…Younger age, gender, higher socio-economic status, better health status and self-rated health, better functional status and cognitive performance and extensive social relationships are some of the factors that may positively contribute to or confound and modify the associations of activity and subjective well-being (Beekman et al, 1998;Cummings, 2002;Diener, 1984;Everard, 1999;Heidrich, 1993;Heikkinen, Berg, & Avlund, 1995;Palsson & Skoog, 1997;Tijhuis, De Jong-Gierveld, Feskens, & Kromhout, 1999). The intensity of these associations has varied in different studies.…”
Section: Introductionmentioning
confidence: 92%
“…HIV symptoms were measured with the 21-item HIV Symptoms Experience Inventory, an instrument developed to assess HIV symptoms specific to women (Bova, 2001). Number of health problems was assessed with the Health Problems Measure, which asks whether respondents have any of 19 health problems and the extent to which each health problem interferes with activities of daily living (Duke University, 1978;Heidrich, 1993). The Subjective Health Measure was used to measure perception of health.…”
Section: Instrumentsmentioning
confidence: 99%
“…Hispanic women, followed by African American women, reported a high level of social support. This pattern has several possible explanations: Older women who have higher levels of functional health are also better able to maintain a support network of family and friends (Heidrich, 1993;Krause, Liang, & Yatomi, 1989); Hispanic and Black people attribute more importance to family relationships than White people do (Vaux, 1985), and this support has often helped them bridge the gap between the dominant culture and their own culture (Sotomayor & Applewhite, 1988); and, Black women typically draw on multiple sources of support to help them with their hardships (Kaye, 1995;Ulbrich & Bradsher, 1993). One contradiction noted in the Established Populations for Epidemiologic Studies of the Elderly (EPESE) study is that African Americans reported fewer close relatives and higher rates of not seeing their relatives monthly than the Whites reported (Cornoni-Huntley, Brock, Ostfeld, Taylor, & Wallace, 1992).…”
Section: Discussionmentioning
confidence: 92%
“…In other studies, physical health has been shown to not only affect other dimensions of functional status (Ailinger, Dear, & Holley-Wilcox, 1993;Heidrich, 1993;Palmore et al, 1985) but also to predict institutionalization and mortality (Reuben, Siu, & Kimpau, 1992;Wolinsky, Callahan, Fitzgerald, & Johnson, 1993). Therefore, it is not surprising to find that it was the only predictor of service need and use with our older women.…”
Section: Discussionmentioning
confidence: 96%